SISTEM INFORMASI PENDAFTARAN SISWA BARU MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT PADA TK PERMATA HATI BEKASI - Aini, Qurrotu (Jurnal Ilmiah Informatika Global, 2025)
TK Permata Hati Bekasi still relies on a manual system for new student registration, using paper-based forms and brochures as the primary sources of information. This method is considered inefficient, time-consuming, prone to data recording errors, and makes it difficult for parents to obtain accurate and up-to-date information quickly. In line with the advancement of information technology, there is a need for a system that supports digitalization to improve work efficiency and information services. This study aims to design and develop a web-based information system for new student registration. The method used is Rapid Application Development (RAD), which includes the stages of requirements planning, system design, development, and implementation. The developed system features an online registration form, document upload functionality, applicant data management, and registration confirmation notifications. System testing was conducted using the Black Box Testing method to ensure that all functions work as expected by users. The results of this study indicate that the system can improve the efficiency of the registration process, provide easy online access for parents, and assist school administration in managing student data in a systematic, fast, and accurate manner. Therefore, this system is expected to serve as a digital solution that supports the student registration process at TK Permata Hati Bekasi.